A new species of Guatteria (Annonaceae) endemic to the Atlantic Forest of Brazil - Lobão, Adriana; Lopes, Jenifer (Phytotaxa, 2014)
One of the most important families in terms of species richness in the Atlantic Forest and other lowland tropical forests is Annonaceae (Leitão-Filho 1987, Ter Steege et al. 2000), among which Guatteria is one of the largest genera with 211 species (Maas et al. 2011); it is also one of the most diverse genera of Neotropical trees. Erkens et al. (2007) stated that an updated revision is needed, and Lobão et al. (2012) revised the species of the Brazilian Atlantic Forest.